Danish mothers of young children adhere less to international physical activity guidelines compared with mothers of older children - Solvej Videbæk Bueno; Sebastian Deisting Skejø; Rasmus Oestergaard Nielsen; Knud Ryom; Per Kallestrup; Peter Elsborg; Christina Bjørk Petersen; Julie Sandell Jacobsen (Preventive Medicine Reports)
Introduction: This study aimed to investigate if the prevalence proportion of non-adherence to the World Health Organization (WHO) guidelines of a minimum of 150 minutes of moderate-to-vigorous physical activity per week varied among mothers based on the age of their youngest child. Additionally, the study aimed to investigate whether such association varied by parity. Methods: The population-based design used self-reported physical activity data on 8774 Danish mothers who participated in the Danish National Health Survey 2021. The primary outcome was weekly hours of moderate-to-vigorous physical activity, dichotomized into adherers or non-adherers to WHO guidelines. Results: The prevalence proportions of non-adherence ranged from 60 % to 70 %. Significantly higher prevalence proportions of non-adherers were observed among mothers of infants and toddlers aged 0–3 years compared with mothers of school-age children. When stratified by parity, multipara mothers with infants aged 0–6 months reported the highest prevalence proportion (74 %) of non-adherence among all subgroups. Conclusion: Due to the health benefits derived from adequate levels of physical activity, the large proportion of mothers not adhering to the WHO physical activity guidelines is a public health concern. The findings of the present study suggest a need for improving interventions and policies to enhance physical activity levels in mothers, especially mothers of infants and toddlers.